ISOLASI, KARAKTERISASI BAKTERI ASAM LAKTAT, DAN ANALISIS PROKSIMAT DARI PANGAN FERMENTASI “TEMPOYAK” - Arina Aisyah; Endang Kusdiyantini; Agung Suprihadi (Jurnal Akademika Biologi, 2014)
Tempoyak is a food made from fermented durian flesh with the addition of salt and brooded for seven days. Tempoyak quality is strongly influenced by the presence of microbes involved during the process of fermentation. This study aimed to isolate and characterize lactic acid bacteria (LAB) that play a role in the tempoyak fermentation process, and to perform proximate analysis of the durian and tempoyak. Isolation was done on 0, 3rd, 5th, and 7th day fermentation with streak methods. The isolates then underwent morphology and motility observation, biochemical tests, and proximate analysis.  The isolation of tempoyak resulted seven isolates of bacteria that had different colony and cell morphology. Gram staining of the bacterial cell produced a purple color with the rod and spherical shape. Motility test resulted non motile bacteria. Catalase test of bacteria isolates produced negative catalase. Isolates showed positive results in test for acid production and carbohydrate fermentation. pH decrease from 6.88 to 5.74 on the last day of brooding. Seven isolates obtained had characteristics that were similar with the characteristic of LAB, which was Gram positive, rod shaped or spherical, non motile, negative catalase, and produce acid. Tempoyak nutrient contained, ie 15.12% moisture content, 27.03% ash content, 2.69% fat content, 6.37% protein content, and 48.79% carbohydrate content. Keywords: tempoyak, LAB, morphology, biochemistry, proximate